К созданию системы мониторинга риск-ситуаций на искусственных водных объектах - Levkevich Виктор; Malashevich Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
On the base of the analysis of conditions of a number of hydro technical constructions situated on water reserves of the Republic of Belarus proposals are given concerning the structure of monitoring system of risk-situations on such objects. The proposals according to the conception of its building are given.